Improvement of high voltage direct current material properties upon tailoring the morphology of crosslinked polyethylenes. Issue 6 (12th September 2021) - Niedik, Christoph Felix; Jenau, Frank; Maricanov, Michail; Segiet, Dominik; Tiller, Joerg Christian; Katzenberg, Frank
Abstract: Crosslinked linear low‐density polyethylene (XLPE) is the most common polymeric cable insulation material for high‐voltage applications with a high number of operating hours in high voltage alternating current (HVAC) systems. High voltage direct current (HVDC) power transmission and polymeric cable systems play a major role in the future and raise, besides numerous systemic benefits, challenges in the design of material properties. The main issue is injection and trapping of space charges in insulation materials under DC‐fields. The objective of this work is to increase knowledge of the interplay between microstructure and material performance of XLPE under DC by tailoring its morphology beyond the capabilities of "common crystallization kinetics" upon constrained crystallization at certain elongations. It was found that the tailored oriented morphology influences the energetic depth of traps and a significant reduction of space charge density occurs. Moreover, the optimized oriented morphology leads to a significant reduction of field enhancement for field strengths E Laplace  ≥ 20 kV mm −1 compared to unoriented XLPEs with spherulitic morphology. It is shown that this way of morphology tailoring results in a considerable, material dependent reduction of field exposure by a factor of 4, which promises a significant improvement in the electrical life time of polymeric insulation material used. Abstract : A key experiment demonstrates that tailoring the morphology of XLPE offers enormous potential to favorably influence the space charge accumulation under HVDC fields. It is shown that crystallizing XLPE constrained to an optimized oriented morphology already reduces the field exposure by a factor of 4.